1994
DOI: 10.1111/j.1365-2362.1994.tb02185.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipids in HIV‐infected patients: a prospective study in 95 patients

Abstract: The present study aimed to determine plasma lipid levels in 95 HIV-infected patients divided into four groups according to the CD4 lymphocyte counts comparatively to a control group of 20 HIV-negative normolipidaemic subjects. A relationship between lipidic abnormalities and immune or nutritional status was also investigated. The patients below 200 CD4 lymphocyte mm-3 (groups 1 and 2) had significantly lower total cholesterol than the controls. The patients below 400 CD4 lymphocytes mm-3 (groups 1, 2, 3) had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
91
1
7

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(110 citation statements)
references
References 14 publications
(7 reference statements)
11
91
1
7
Order By: Relevance
“…Before widespread HAART use, elevated triglyceride and low HDL-C levels were reported in HIV infection [11,12]. In the HAART era, several studies have shown higher total cholesterol, LDL-C and triglyceride levels associated with PI use [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before widespread HAART use, elevated triglyceride and low HDL-C levels were reported in HIV infection [11,12]. In the HAART era, several studies have shown higher total cholesterol, LDL-C and triglyceride levels associated with PI use [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…High total cholesterol and triglyceride levels have also been reported in patients on non-PI HAART regimens [9,10]. In addition, low high-density lipoprotein (HDL-C) levels and hypertriglyceridaemia have been described in HIV-infected patients not receiving antiretroviral therapy [11][12][13]. …”
mentioning
confidence: 99%
“…Constans et al 29 actually observed prognostic implication of these alterations. The lower the TCD4+ lymphocytes count, the higher the triglycerides level and the lower the HDL-cholesterol levels.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the predisposition to atherosclerosis results from cumulative exposure to the virus and from metabolic changes secondary to the use of PI, thus determining an unfavorable metabolic profile characterized by hypertriglyceridemia, low HLD-c and insulin resistance observed in 25 to 60% of the patients 6 .…”
Section: Introductionmentioning
confidence: 99%